International definition of a point-of-care test in family practice: a modified e-Delphi procedure. (29th January 2018) - Schols, Angel M R; Dinant, Geert-Jan; Hopstaken, Rogier; Price, Christopher P; Kusters, Ron; Cals, Jochen W L
Abstract: Background: The use of point-of-care tests (POCTs) in family practice is increasing, and the term POCT is often used in medical literature and clinical practice. Yet, no widely supported definition by several professional fields exists. Objective: To reach consensus on an international definition of a POCT in family practice. Methods: We performed a modified international e-Delphi procedure of four rounds among expert panel members from different professional backgrounds—family practitioners, laboratory specialists, policymakers, researchers and manufacturers. Results: Of 27 panel members from seven different countries, 26 participated in all rounds. Most panel members were active in POCT research or policymaking and 70% worked in family medicine. After choosing important components, structuring of answers and feedback, the following definition was chosen as the best or second best definition by 81% of panel members: a point-of-care test in family practice is a test to support clinical decision making, which is performed by a qualified member of the practice staff nearby the patient and on any part of the patient's body or its derivatives, during or very close to the time of consultation, to help the patient and physician to decide upon the best suited approach, and of which the results should be known at the time of the clinical decision making. Conclusion: The definition emerging from this study can inform family practitioners, laboratory specialists, policymakers and manufacturers on the most widely supported and recognized definition and could act as a clear starting point for the organization and execution of professional point-of-care testing in family practice worldwide.